2021
DOI: 10.1186/s12992-021-00723-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mining projects on water and sanitation infrastructures and associated child health outcomes: a multi-country analysis of Demographic and Health Surveys (DHS) in sub-Saharan Africa

Abstract: Background Access to improved water and sanitation infrastructures are key determinants of health. The sub-Saharan African region in particular is lagging behind the ambitious goal of the 2030 Agenda for Sustainable Development to ensure universal access to improved and reliable water and sanitation for all (Sustainable Development Goal (SDG) 6). Large mining projects can promote economic growth and hence investments in water and sanitation infrastructures, but at the same time lead to rapid po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 48 publications
(57 reference statements)
0
18
0
Order By: Relevance
“…In line with this hypothesis, it is argued that the size of primary exports by mines increases in later stages during the resource extraction phase [ 36 , 37 ]. Consequently, they may contribute more to local and national economic growth and potentially ramp up corporate social responsibility activities, such as investments in local water and sanitation infrastructures [ 8 , 36 , 38 , 39 ]. Overall, these results suggest that the impact of mining projects on local development [ 6 , 40 , 41 ] might be an opportunity for African countries to work towards the ambitious target of the 2030 Agenda for Sustainable Development to curb infant and under-five mortality [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In line with this hypothesis, it is argued that the size of primary exports by mines increases in later stages during the resource extraction phase [ 36 , 37 ]. Consequently, they may contribute more to local and national economic growth and potentially ramp up corporate social responsibility activities, such as investments in local water and sanitation infrastructures [ 8 , 36 , 38 , 39 ]. Overall, these results suggest that the impact of mining projects on local development [ 6 , 40 , 41 ] might be an opportunity for African countries to work towards the ambitious target of the 2030 Agenda for Sustainable Development to curb infant and under-five mortality [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies examine the effect of mines on child morbidity and malnutrition [ 8 , 14 , 17 ]. Using similar data, Dietler and colleges found no effect of mining activities on diarrhoea prevalence [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the importance of large mining operations for regional economic development, mining also has the potential to improve other indicators targeted by the Sustainable Development Goals (SDGs)-most importantly population health. Recent studies have found positive links between resource rents and life expectancy at the country level [4], and linked resource extraction projects to reduced prevalence of undernutrition and infectious disease [5,6] as well as to reduced incidence of acute and chronic health conditions [7]. Evidence from Ghana [8,9], Tanzania [9] and Sub-Saharan Africa (SSA) at large [10] also suggests lower infant mortality in regions with mining projects.…”
Section: Introductionmentioning
confidence: 99%